2009
DOI: 10.1002/humu.20933
|View full text |Cite
|
Sign up to set email alerts
|

Antisense therapeutics for neurofibromatosis type 1 caused by deep intronic mutations

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder affecting 1:3,500 individuals. Disease expression is highly variable and complications are diverse. However, currently there is no specific treatment for the disease. NF1 is caused by mutations in the NF1 gene, approximately 2.1% of constitutional mutations identified in our population are deep intronic mutations producing the insertion of a cryptic exon into the mature mRNA. We used antisense morpholino oligomers (AMOs) to restore normal splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…19 Later this technology was used successfully for other diseases like cystic fibrosis 20 or more recently for NF1. 21 Today, different pre-clinical and clinical splice-modulating therapies using AONs, like restoring open reading frames, influencing alternative splicing or inducing exon inclusion, have been successfully used for many different genetic disorders. 16,17 In this study, we report a NF2 patient with bilateral vestibular schwannoma who was found to bear a deep intronic mutation in the NF2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…19 Later this technology was used successfully for other diseases like cystic fibrosis 20 or more recently for NF1. 21 Today, different pre-clinical and clinical splice-modulating therapies using AONs, like restoring open reading frames, influencing alternative splicing or inducing exon inclusion, have been successfully used for many different genetic disorders. 16,17 In this study, we report a NF2 patient with bilateral vestibular schwannoma who was found to bear a deep intronic mutation in the NF2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Alleles with intronic mutations activating cryptic splicing sites are potentially correctable with antisense oligonucleotides to prevent the splicing machinery from recognizing the cryptic exon and promote normal splicing, as successfully shown in several genetic disorders (42)(43)(44). Similar antisense oligonucleotides may also apply to GS patients bearing deep intronic mutations and can be first tested on the leukocytes expressing NCC mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Once regarded as junk DNA, intronic and intergenic sequences are now perceived to contain crucial splicing machinery elements and other gene expression regulating motifs. Recently, several studies have shown that mutations disturbing these important elements can lead to disease [34][35][36][37]. Therefore, we expect that high throughput sequencing of the entire 3.3 Mb candidate region might reveal a more complex mutation associated with DLB in family DR246.…”
Section: Discussionmentioning
confidence: 99%